P452 Tofacitinib Effectiveness and Safety as Therapy for Ulcerative Colitis. (21st January 2022) - McNally, M; Keating, E; Gray, E; McCormick, E; Carroll, A; Palmer, C; Kennedy, U; McKiernan, S; MacCarthy, F; Dunne, C; Hartery, K; Egan, L; et al.
Abstract: Background: Tofacitinib is an oral small molecule directed against the JAK/STAT pathway. It is the first JAK inhibitor approved for the treatment of ulcerative colitis (UC) and is licenced for use in moderate to severely active disease. This study aims to evaluate tofacitinib effectiveness and safety in real-world clinical practice for moderate-to-severely active UC. Methods: Consecutive patients receiving Tofacitinib for UC in four Irish tertiary referral centres were identified. Baseline clinical data and information on therapy outcomes were collected by retrospective review of electronic patient records. Patients included in the study cohort were older than 18 years of age, had a confirmed diagnosis of UC, had received at least one induction dose of tofacitinib, and had available clinical follow-up. The primary study endpoint was 6-month corticosteroid-free remission rate. Secondary endpoints included 3-month clinical response, inflammatory biomarkers responses to tofacitinib therapy, rates of tofacitinib discontinuation, and side effects. Continuous variables are presented as median [range]. P values < 0.05 were considered significant in all analyses. Results: Fifty-three UC patients were included; age 40.4 [33.3 – 53.9] years, 66% male, disease duration 5.7 [2.6–10.9] years; follow-up 8.7 [6.4–14.1] months. 43%, 40% and 17% of patients had extensive, left-sided disease and proctitis respectively. At baseline, clinical Mayo subscore was 7 [5–8], CRP 4.0 [1.0–16.7] mg/L and faecal calprotectin 914 [444.0–1000] mcg/g. The 3-month clinical response and 6-month corticosteroid-free remission rates were 69% and 43%, respectively. Following tofacitinib therapy, compared with baseline values, a significant reduction in 3-month clinical Mayo score, 3-month CRP, and post-induction faecal calprotectin was observed, p <0.03 for all comparisons. 36% of patients (n=19) discontinued tofacitinib during study follow-up (time to Tofacitinib discontinuation 1.9 [0.5–18.9] months). Side effects occurred in 26% percent of patients with the majority minor and self-limiting. No cardiovascular or venous thromboembolic events were observed and no hospitalisations occurred due to therapy-related side effects Conclusion: These data are in concordance with prior studies of tofacitinib effectiveness and safety in real world practice. They demonstrate that, in a cohort of UC patients with significant prior therapy exposure, tofacitinib is an effective therapy with an acceptable safety profile.